2018
DOI: 10.1080/09540121.2018.1537463
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of depression among caregivers of children living with HIV in Ghana: findings from the Sankofa pediatric disclosure study

Abstract: Prior studies show an association between caregiver depression and child health outcomes. There has been little examination of depression among caregivers of HIV-infected children in sub-Saharan countries where pediatric HIV is concentrated. Using baseline data collected in the pediatric HIV disclosure intervention trial, Sankofa, we examined the prevalence and factors associated with depression among caregivers (N=446) of children infected with HIV in Ghana. Data were analyzed with descriptive and regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 74 publications
(77 reference statements)
3
5
1
Order By: Relevance
“…We also observed a lower rate of caregiver depression in our PHIV group than observed in African studies. . No association was found between caregiver depression and developmental outcomes in our study, although such associations have been observed in earlier studies .…”
Section: Discussioncontrasting
confidence: 69%
“…We also observed a lower rate of caregiver depression in our PHIV group than observed in African studies. . No association was found between caregiver depression and developmental outcomes in our study, although such associations have been observed in earlier studies .…”
Section: Discussioncontrasting
confidence: 69%
“…At each time point, adjusted mean BDI scores were consistently lower for caregivers of children who had completed the disclosure process. Caregivers of children living with HIV have been found to have a high prevalence of depression symptoms, and our findings suggest disclosure may help to alleviate the burden in this high-risk group [37,38]. Interestingly, we also found CDI scores in the current study to be significantly correlated with the BDI scores of caregivers (r = 0.19, p = 0.019).…”
Section: Discussionsupporting
confidence: 68%
“…At each time point, adjusted mean BDI scores were consistently lower for caregivers of children who had completed the disclosure process. Caregivers of children living with HIV have been found to have a high prevalence of depression symptoms, and our ndings suggest disclosure may help to alleviate the burden in this high-risk group [36,37]. Interestingly, we also found CDI scores in the current study to be signi cantly correlated with the BDI scores of caregivers (r = 0.19, p = 0.019).…”
Section: Discussionsupporting
confidence: 65%